A Knowledge Approach for E-Goverment Strategic Planning - Faras Zuheir, (2004)
This thesis introduces a strategic planning approach for e-goverment from a proposed knowledge persspective that customize a felicitous definition of strategic planning within the e-goverment context. This is done by providing answers for the problem of knowledge acquisition, modeling, representation, processing and interpretation taking place within its flow.